Developing of HEC/PVA fibers with cellulose nanocrystal as a bone tissue engineering scaffold - Zulkifli, Farah Hanani (2020)
Biomaterial is a medical terminology that used to describe all natural or synthetic resources such as polymer that are useful in the introduction of living tissue as part of medical device or implant without causing any adverse of immune rejection reaction. Cellulose has been extensively explored over decades as one of the biomaterials used in tissue engineering application due to their unique properties which are low cost, good biocompatibility and good mechanical properties. Preparation of cellulose nanocrystal (CNC) from cellulose pulp is an alternative way to fulfil the CNC demand. In tissue engineering, replacement or regeneration of damaged bone is a major challenge in orthopedic surgery. Hence, scaffold-based bone tissue engineering designs to overcome these bone defects. This report comprised of two parts. The first part is about the fabrication and characterization of CNC while the second part is the fabrication and characterization of scaffolds including in vitro degradation and cell culture studies. In this present work, CNC produced from empty fruit bunch (EFB) were successfully fabricated by acid hydrolysis. Cellulose pulps were heated at 85 °C in 65 % of sulphuric acid. The cellulose suspension was diluted, centrifuged, sonication, and then undergoes freeze-drying to obtain CNC. CNC acts as nanofillers in scaffolds will be physically, chemically and thermally characterized by using field emission scanning electron microscope (FESEM), attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR) and differential scanning calorimetry (DSC). FESEM results showed that CNC appeared in spherical shape with particle dimension in the range between 5 to 30 nm in diameter. The absorption spectra of CNC appeared in specific bands which are at 1045, 1346, 1637, 2903, and 3391 cm^(-1). DSC thermograms shows that melting temperature, T_m is occur at 197.1 °C, while the glass transition temperature, T_g is 65.2 °C. Next, a porous three-dimensional (3D) scaffold of HEC/PVA and HEC/PVA/CNC were successfully fabricated by freeze-drying technique. HEC (5 wt%) and PVA (15 wt%) were dissolved and blended at a ratio of 50:50 and incorporated with various concentration of CNC (1, 3, 5 and 7 wt%). The morphology, mechanical and thermal properties of scaffolds were characterized by SEM, ATR-FTIR, DSC, thermogravimetric (TGA), and universal tensile machine (UTM). The degradation behaviors of scaffolds were characterized by a series of analysis including swelling ratio, weight loss and pH changes. Meanwhile, cytotoxicity studies on both porous scaffold biomaterials were carried out by utilizing human fetal osteoblast (hFOB) cells using MTT assays and cell-scaffold morphological study. Incorporated HEC/PVA with CNC were exhibited superior functionality which resulted in decreasing average pore size and there were some slightly changes in the chemical structure as determined by FTIR spectra. Thermal studies revealed that the melting temperatures of HEC/PVA/CNC scaffold were slightly shifted to a higher value. Furthermore, it can be seen that addition of CNC resulted in increases in the ultimate tensile stress (from 0.25 to 0.92 MPa) and ultimate tensile strain (from 5.83 to 11.03 MPa). Hence, it offers a very good mechanical performance. The cell culture study revealed that the hFOB cells were able to attach and spread on all scaffolds and supported the cell adhesion and proliferation. The optimum concentration of CNC is best found at 3 and 5 wt% and further addition of CNC reduced the cell viability. Due to its biocompatible and biodegradable properties, these newly developed highly porous scaffolds may provide a promising alternative scaffolding matrix for bone tissue engineering regeneration.